Diagnostic challenge of scrub typhus-induced myocarditis in a postpartum patient in primary healthcare: a case report - Silwal, Mahesh (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Scrub typhus is a zoonotic disease caused by the bacteria named Orientia tsutsugamushi. Recently, it has become one of the greatest public health concerns in the Asia-Pacific countries, particularly in rural tropical regions. The diagnosis is largely clinical; however, varied clinical presentation is not uncommon, which leads to delayed diagnosis and treatment. Myocarditis is a rare complication and, if not treated early, can lead to heart failure and cardiogenic shock. A comprehensive case report will be discussed in this article to highlight the diagnostic dilemma scrub typhus presents. Prompt treatment with antimicrobial is the cornerstone of the management, which rapidly improves the symptoms, as seen in the case described in this article.